Decreased re-conviction rates of DUI offenders with intensive supervision and home confinement. (2nd November 2017) - Barta, William D.; Fisher, Virginia; Hynes, Patrick
ABSTRACT: Background : In some jurisdictions, persons who are convicted of driving under the influence of alcohol (DUI) are allowed to serve some portion of their prison sentence under home confinement as part of Intensive Supervision Programs (ISPs) which include pre-release psycho-education and close post-release supervision. Objectives : Test the hypothesis that persons convicted of DUI offenses who have spent some portion of their sentence under home confinement, as compared to a historical comparison group, will exhibit a relatively low re-conviction rate. Methods : Using administrative data for 1, 410 repeat DUI offenders (302 members of the historical comparison group, 948 ISP members, and 160 persons who appear in both groups at different points in time), with a follow-up period of up to 3 years and 10 months, a marginal Cox model was employed to compare conviction rates of persons who experienced intensive supervision and home confinement with historical comparison group members. Results : Persons with ISP + home confinement experience a re-conviction rate that is less than half that observed in the comparison group. Age, ethnicity (white vs. non-white), and gender are also significant predictors of re-conviction. Conclusion : Home confinement, in conjunction with psycho-education and other program elements, is one means of reducing the costs of incarceration. The results of this study suggest that, in addition to cost savings, states may realize a public safety benefit in the form of a reduction in DUI offense rates.